PENDAMPINGAN PENCATATAN KEUANGAN BERBASIS TEKNOLOGI, PENERAPAN SAK ETAP DAN SIMULASI AUDIT KEUANGAN UNTUK USAHA KONVEKSI CV PHOSPHORUS BORNEO: MEWUJUDKAN TRANSPARANSI, AKUNTABILITAS DAN KEBERLANJUTAN BISNIS - Emayanti Christina Hutabarat; Diah Fitri Harseno; Desy Natalia; LM Hasriadi (Yayasan Nuraini Ibrahim Mandiri, 2025)
The accelerating pace of economic growth necessitates that business practitioners possess a comprehensive understanding of financial recording in accordance with applicable accounting standards, proficiency in accounting technology, and foundational knowledge of financial auditing. Financial statements play a pivotal role in presenting the financial position of a business entity and serve as a critical basis for strategic decision-making. Accordingly, the awareness and capacity to prepare accountable and transparent financial reports must be continuously enhanced, particularly in the garment sector, as exemplified by CV Phosphorus Borneo. Despite its importance, the adoption of technology-based accounting systems for transaction recording remains limited among business operators. This community engagement program aimed to provide technical assistance and education on the preparation of financial statements in accordance with SAK ETAP, the introduction of the Accurate accounting system, and fundamental insights into the role of financial auditing in ensuring business sustainability. The outcomes of this initiative indicate significant improvements in participants’ capabilities in financial reporting under SAK ETAP, increased proficiency in utilizing technology-based accounting systems, and enhanced understanding of financial audits. It is anticipated that similar community service activities will be continuously implemented to strengthen the resilience and competitiveness of business sectors in facing dynamic economic challenges. Keywords: Financial recording, accounting system, SAK ETAP, community engagement.